A history of ancient Near Eastern law. - Westbrook, Raymond; Beckman, Gary M. (Handbuch der Orientalistik. Nahe und der Mittlere Osten ;, 2003)
The history of law can only begin after the written record of it commences; in the Middle East, that is a few centuries after the advent of writing itself in the fourth millennium BCE. That law is the oldest recorded, and is the foundation of the two great modern Western systems, the Common Law and the Civil Law. In sections covering the next three.